A method for preparing a composite solid electrolyte membrane

By adopting a three-layer composite solid electrolyte membrane, using ultrasonic filling technology and hot pressing molding, the existing solid electrolyte membrane is solved by not being heat-resistant and low mechanical strength under high temperature conditions, achieving the effects of high mechanical strength, high ionic conductivity and good thermal stability, and improving the performance and safety of all-solid-state batteries.

CN119764533APending Publication Date: 2025-04-04ZHEJIANG HEXIN NEW MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411947877.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing solid electrolyte membrane is not heat-resistant under high temperature conditions, which can easily lead to membrane melting and cause battery short circuits and explosions. Its low mechanical strength and poor ionic conductivity limit the performance improvement and commercialization of all-solid-state batteries.

Method used

A composite solid electrolyte membrane with a three-layer structure is adopted. The first layer is an oxide-polymer-containing composite solid electrolyte layer, the second layer is a sulfide solid electrolyte layer, and the third layer is a polysiloxane-based solid electrolyte layer. Through ultrasonic filling technology and hot pressing molding, the mechanical strength and interlayer binding force of the film are enhanced.

Benefits of technology

It effectively improves the interface contact between the solid electrolyte and the positive and negative electrodes, reduces the interface impedance, improves mechanical strength, ionic conductivity and thermal stability, inhibits the growth of lithium dendrites, and enhances the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a method for preparing a composite solid electrolyte membrane, the composite solid electrolyte membrane comprises three layers, the first layer is a composite solid electrolyte layer containing oxide-polymer, the second layer is a sulfide solid electrolyte layer, and the third layer is a polysiloxane solid electrolyte layer; the preparation method comprises the following steps: S1, preparation of the first layer: immersing a polymer porous membrane as a substrate into the first layer slurry, coordinating ultrasound to make the first layer slurry fully fill the pores, and drying to obtain; S2, preparation of the second layer: coating the second layer slurry on the basis of the first layer, drying to obtain; S3, preparation of the third layer: coating the third layer slurry on the basis of the second layer, drying to obtain; S4, pressing: the first, second and third layers are hot-pressed by rollers to obtain. The composite solid electrolyte membrane of the present invention can effectively improve the interface contact between the solid electrolyte and the positive and negative electrodes, reduce the interface impedance, and has the characteristics of high mechanical strength, high ionic conductivity, good thermal stability, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytes, and in particular relates to a method for preparing a composite solid electrolyte membrane. Background Art

[0002] Solid electrolyte membranes play a core role in lithium-ion batteries and other energy storage devices. Compared with traditional liquid electrolytes, solid electrolytes provide higher safety and energy density. In recent years, researchers have made major breakthroughs in the development of solid electrolyte materials. Solid electrolytes are mainly divided into polymer electrolytes, oxide electrolytes, halide electrolytes and sulfide electrolytes. Among them, polymer electrolytes have good flexibility, easy film formation, simple preparation process, and good interface wettability with electrodes, but their room temperature ionic conductivity is low (<10 -5 S / cm), which seriously affects the performance of the battery; oxide electrolytes have high ionic conductivity (10 -4 ~10 -3 S / cm), with a wide electrochemical window, but its brittleness is large and the interface contact with the electrode is poor, which seriously limits its practical application; halide electrolytes have high ionic conductivity (10 -4 ~10 -3 S / cm) and a wide electrochemical window, but it is sensitive to moisture, easily degraded in air, and unstable to lithium metal; sulfide solid electrolytes have high ionic conductivity (10 -3 ~10 -2 S / cm) and become the most promising solid electrolyte. However, sulfide solid electrolytes have a narrow electrochemical window, are unstable to lithium metal, and are sensitive to air and moisture, which limits their practical application. Therefore, the development of multi-component composite solid electrolyte membranes with comprehensive advantages makes it possible to improve the performance and commercialize all-solid-state batteries.

[0003] The future of solid electrolyte membranes will focus on further optimization of material properties and maturity of large-scale production technology. Traditional diaphragm base membranes are not resistant to high temperatures due to low porosity and intrinsic defects of high molecular polymers, which can easily cause the diaphragm to melt, resulting in short circuits between the positive and negative electrodes of the battery, and even serious accidents such as battery explosions and vehicle fires. Some composite solid electrolyte membranes are prone to problems such as lithium dendrite growth, low mechanical strength, and poor ion conductivity, while the use of sulfide solid electrolyte membranes has the disadvantages of being unstable to lithium metal and sensitive to air and moisture. Summary of the invention

[0004] In order to solve the shortcomings of single-layer or double-layer solid electrolyte membranes, the present invention provides a method for preparing a composite solid electrolyte membrane, which has a three-layer structure, can effectively improve the interface contact between the solid electrolyte and the positive and negative electrodes, reduce the interface impedance, and has the characteristics of high mechanical strength, high ionic conductivity, and good thermal stability.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a composite solid electrolyte membrane, wherein the composite solid electrolyte membrane comprises three layers, the first layer is a composite solid electrolyte layer containing an oxide-polymer, the second layer is a sulfide solid electrolyte layer, and the third layer is a polysiloxane-based solid electrolyte layer; the preparation method comprises the following steps:

[0007] S1, preparation of the first composite solid electrolyte layer:

[0008] Immersing a polymer porous membrane as a substrate into the first layer of slurry, using ultrasound to allow the first layer of slurry to fully fill the pores of the polymer porous membrane, and drying to obtain the composite solid electrolyte layer;

[0009] S2, preparation of the second sulfide solid electrolyte layer:

[0010] Coating a second layer of slurry on the basis of the first layer, and drying, to obtain the sulfide solid electrolyte layer;

[0011] S3, preparation of the third polysiloxane-based solid electrolyte layer:

[0012] Coating a third layer of slurry on the basis of the second layer, and drying, to obtain the polysiloxane-based solid electrolyte layer;

[0013] S4, Pressing:

[0014] The first, second and third layers are rapidly hot-pressed by rollers at a certain temperature to obtain the composite solid electrolyte membrane.

[0015] In the above technical solution, in S1, the first layer of slurry includes an oxide solid electrolyte, a polymer solid electrolyte, a lithium salt and a first solvent, wherein the mass ratio of the oxide solid electrolyte, the polymer solid electrolyte and the lithium salt is (30-50): (30-50): (50-100).

[0016] In the above technical solution, in S2, the second layer slurry includes a sulfide solid electrolyte, a first polymer, a lithium dendrite eliminator and a second solvent, wherein the mass ratio of the sulfide solid electrolyte, the first polymer and the lithium dendrite eliminator is (45-99): (1-3): (1-5).

[0017] In the above technical solution, in S3, the third layer slurry includes polysiloxane, the second polymer and lithium salt, wherein the mass ratio of the third layer slurry including polysiloxane, the second polymer and the lithium salt is (20-80):50:50.

[0018] In the above technical solution, the oxide solid electrolyte is Li 1+a Al a Ti 2-a (PO4)3(LATP, 0≤a≤0.5), Li 1+b Al b Ge 2-b (PO4)3(LAGP, 0≤b≤0.65), La 2 / 3-c Li 3c TiO3(LLTO,0.04 <c<0.17)、La 0.56 Li 0.33+d Ti 1-d Al d O3(LLTAO, 0≤d≤0.06), Li7La3Zr2O 12 (LLZO), Li 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO) and Li 6.75 LqCy 1.75 Nb 0.25 O 12 At least one of (LLZONb);

[0019] The polymer solid electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI);

[0020] The first solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), acetonitrile (ACN) and dimethyl sulfoxide (DMSO).

[0021] In the above technical scheme, the lithium salt is at least one of LiTFSI, LiFSI, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, LiBF4, LiBF3(C2F5), LiSCN, LiN(CN)2, LiDFOB, LiODFB, LiN(SO2F)2, LiCF3SO3, LiClO4, LiAsF6 and LiSbF6.

[0022] In the above technical solution, the sulfide solid electrolyte is Li6PS5Cl, Li2S-P2S5, Li4GeS4, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3、Li3PS4、Li7P3S 11 At least one of;

[0023] The first polymer is at least one of styrene-butadiene-styrene elastomer (SEBS), styrene-butadiene-styrene block copolymer (SBS), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), butadiene rubber (BR), natural rubber (NR) and aliphatic polycarbonate (PPC);

[0024] The lithium dendrite eliminator is one or a mixture of two of VO2, TiO2, SiO2, Al2O3, MoS2, VS2, and TiS2;

[0025] The second solvent is at least one of toluene, p-xylene, dichloromethane, dichloroethane, dichloropropane, dibromomethane, dibromoethane, dibromopropane, cyclohexane, n-heptane, n-decane, n-octane and anisole.

[0026] In the above technical solution, the second polymer is at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN).

[0027] In the above technical solution, in S1, the polymer porous membrane is one of a high-porosity PVDF membrane, an ePTFE membrane, a PVDF-HFP membrane, a PAN membrane, and a PMMA membrane, with a porosity of 60-80% and an equivalent pore size of 0.5-10 um.

[0028] In the above technical solution, the thickness of the first layer is 4-10 μm, the thickness of the second layer is 15-30 μm, and the thickness of the third layer is 4-10 μm.

[0029] The beneficial effects of the present invention are:

[0030] 1. The interface bonding technology adopted by the present invention is to fill the first layer of polymer porous membrane, then coat the slurry in sequence to form a whole, and then hot press, which enhances the interface bonding strength between the three layers. Compared with the three-layer membrane formed separately and then hot pressed, the three-layer structure of the composite solid electrolyte membrane prepared by the present invention has uniform thickness, uniform composition, and better interlayer bonding strength.

[0031] 2. The present invention adopts ultrasonic filling technology to densely and evenly fill the solid electrolyte into the pores of the high-porosity polymer porous membrane with the assistance of ultrasound. The surface of the first layer of oxide-polymer composite solid electrolyte layer is smooth and flat, which greatly enhances the mechanical properties of the composite electrolyte membrane and the electrolyte is evenly dispersed.

[0032] 3. By adjusting the thickness ratio of the three-layer structure, the advantages of solid electrolytes of different materials are combined, so that the membrane has the characteristics of high mechanical strength, high ionic conductivity, good thermal stability, and inhibition of lithium dendrite growth, which effectively improves the interface contact between the solid electrolyte and the positive and negative electrodes and reduces the interface impedance.

[0033] 4. The oxide-polymer composite solid electrolyte layer (first layer) corresponding to the positive electrode side has strong antioxidant properties and can be suitable for high-voltage positive electrode systems. The polysiloxane-based solid electrolyte layer (third layer) corresponding to the negative electrode side has a high affinity for metallic lithium and can capture lithium ions on the surface and evenly regulate the lithium ion flux, thereby achieving dendrite-free lithium deposition / stripping and preventing the lithium metal negative electrode from directly contacting the sulfide solid electrolyte in the second layer (sulfide solid electrolyte layer) and causing side reactions.

[0034] 5. The preparation method of the composite solid electrolyte membrane of the present invention is simple in process, compatible with traditional lithium-ion battery process equipment, and is conducive to large-scale production. DETAILED DESCRIPTION

[0035] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.

[0036] The present invention provides a method for preparing a composite solid electrolyte membrane, wherein the composite solid electrolyte membrane comprises three layers, the first layer being a composite solid electrolyte layer containing an oxide-polymer, the second layer being a sulfide solid electrolyte layer, and the third layer being a polysiloxane-based solid electrolyte layer. The design of the three-layer structure can effectively improve the interface contact between the solid electrolyte and the positive and negative electrodes and reduce the interface impedance.

[0037] The first layer is a composite solid electrolyte layer containing oxides and polymers, which can enhance the mechanical strength and thermal stability of the composite solid electrolyte membrane and has a strong ability to resist the formation of lithium dendrites. The second layer is a sulfide solid electrolyte layer, which can enhance ionic conductivity. The third layer is a polysiloxane-based solid electrolyte layer, which can prevent the lithium metal negative electrode from directly contacting the sulfide solid electrolyte in the second layer and causing side reactions. At the same time, polysiloxane has a high affinity for metallic lithium.

[0038] The preparation method of the present invention comprises the following steps:

[0039] S1, preparation of the first composite solid electrolyte layer:

[0040] The polymer porous membrane is used as a substrate and immersed in the first layer of slurry. Ultrasound is used to make the first layer of slurry fully fill the pores of the polymer porous membrane. The membrane is dried to obtain a composite solid electrolyte layer.

[0041] As one embodiment, the first composite solid electrolyte layer is formed by a wet process, with a drying temperature of 25 to 120° C. for 0.5 to 48 hours, an ultrasonic time of 20 to 60 minutes, and an ultrasonic temperature of 0 to 50° C. The film thickness is 1 to 10 μm, preferably 4 to 10 μm.

[0042] As one embodiment, the polymer porous membrane is one of high-porosity PVDF membrane, ePTFE membrane, PVDF-HFP membrane, PAN membrane, and PMMA membrane, preferably PVDF membrane or ePTFE membrane, with a porosity of 60-80% and an equivalent pore size of 0.5-10 um. The thickness of the first layer is preferably 4-10 μm.

[0043] As one embodiment, the first layer slurry includes an oxide solid electrolyte, a polymer solid electrolyte, a lithium salt and a first solvent, wherein the mass ratio of the oxide solid electrolyte, the polymer solid electrolyte and the lithium salt is (30-50): (30-50): (50-100).

[0044] As one embodiment, the oxide solid electrolyte is Li 1+a Al a Ti 2-a (PO4)3(LATP, 0≤a≤0.5), Li 1+b Al b Ge 2-b (PO4)3(LAGP, 0≤b≤0.65), La 2 / 3-c Li 3c TiO3(LLTO,0.04 <c<0.17)、La 0.56 Li 0.33+d Ti 1-d Al d O3(LLTAO, 0≤d≤0.06), Li7La3Zr2O 12 (LLZO), Li 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO) and Li 6.75 LqCy 1.75 Nb 0.25 O 12 At least one of (LLZONb);

[0045] The polymer solid electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI);

[0046] The first solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), acetonitrile (ACN) and dimethyl sulfoxide (DMSO).

[0047] The lithium salt is at least one of LiTFSI, LiFSI, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, LiBF4, LiBF3(C2F5), LiSCN, LiN(CN)2, LiDFOB, LiODFB, LiN(SO2F)2, LiCF3SO3, LiClO4, LiAsF6 and LiSbF6.

[0048] S2, preparation of the second sulfide solid electrolyte layer:

[0049] A second layer of slurry is coated on the basis of the first layer and dried to obtain a sulfide solid electrolyte layer.

[0050] As one embodiment, the second layer uses a dry process, the drying temperature is 60-80°C, 10-48h, the thickness of the second layer is 15-30μm, preferably 25-30μm. The particle size distribution of the sulfide solid electrolyte in the slurry is D50=5.0-10.0μm.

[0051] As one embodiment, the second layer slurry includes a sulfide solid electrolyte, a first polymer, a lithium dendrite eliminator and a second solvent, wherein the mass ratio of the sulfide solid electrolyte, the first polymer and the lithium dendrite eliminator is (45-99): (1-3): (1-5).

[0052] As one example, the sulfide solid electrolyte is Li6PS5Cl, Li2S-P2S5, Li4GeS4, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li3PS4、Li7P3S 11 At least one of the following; the particle size distribution of the sulfide solid electrolyte is D50=5.0-10.0 μm.

[0053] The first polymer is at least one of styrene-butadiene-styrene elastomer (SEBS), styrene-butadiene-styrene block copolymer (SBS), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), butadiene rubber (BR), natural rubber (NR) and aliphatic polycarbonate (PPC);

[0054] The lithium dendrite eliminator is one or a mixture of two of VO2, TiO2, SiO2, Al2O3, MoS2, VS2, and TiS2;

[0055] The second solvent is at least one of toluene, p-xylene, dichloromethane, dichloroethane, dichloropropane, dibromomethane, dibromoethane, dibromopropane, cyclohexane, n-heptane, n-decane, n-octane and anisole.

[0056] S3, preparation of the third polysiloxane-based solid electrolyte layer:

[0057] A third layer of slurry is coated on the basis of the second layer and dried to obtain a polysiloxane-based solid electrolyte layer. As one embodiment, the drying temperature is 60-80° C. for 10-48 hours. The thickness of the third layer is preferably 4-10 μm.

[0058] As one embodiment, the third layer slurry includes polysiloxane, a second polymer and a lithium salt, wherein the mass ratio of the third layer slurry to the polysiloxane, the second polymer and the lithium salt is (20-80):50:50.

[0059] As one embodiment, the second polymer is at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN).

[0060] The lithium salt is at least one of LiTFSI, LiFSI, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, LiBF4, LiBF3(C2F5), LiSCN, LiN(CN)2, LiDFOB, LiODFB, LiN(SO2F)2, LiCF3SO3, LiClO4, LiAsF6 and LiSbF6.

[0061] S4, Pressing:

[0062] The first, second and third layers are rapidly hot-pressed by rollers at a certain temperature to obtain a composite solid electrolyte membrane.

[0063] As one embodiment, the hot pressing temperature is 60-80° C., and the pressure is 15-45 MPa. The thickness of the third layer is 1-10 μm, preferably 4-10 μm.

[0064] Compared with forming three layers of membranes separately and then hot pressing them, the advantages of the present invention are that the three-layer structure of the solid electrolyte membrane has uniform thickness, uniform composition and better interlayer bonding strength.

[0065] S5, rolling up the dried finished product.

[0066] The composite solid electrolyte membrane prepared by the present invention can be widely used in solid-state lithium batteries, and is suitable for portable devices, electric vehicles and long-endurance energy storage devices.

[0067] Example 1

[0068] A method for preparing a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising three layers, the first layer being an oxide-polymer composite solid electrolyte layer, the second layer being a sulfide solid electrolyte layer, and the third layer being a polysiloxane-based solid electrolyte layer; the preparation method comprising the following steps:

[0069] S1, preparation of the first composite solid electrolyte layer:

[0070] The polymer porous membrane is used as a substrate and immersed in the first layer of slurry, and the first layer of slurry is used to fully fill the pores of the polymer porous membrane with ultrasound, and then dried to obtain a composite solid electrolyte layer. The thickness of the first layer is 4 μm.

[0071] The polymer porous membrane is a high-porosity PVDF membrane with a porosity of 60-80% and an equivalent pore size of 0.5-10 um.

[0072] The first layer of slurry includes an oxide solid electrolyte, a polymer solid electrolyte, a lithium salt and a first solvent, wherein the mass ratio of the oxide solid electrolyte, the polymer solid electrolyte and the lithium salt is 30:30:50.

[0073] The oxide solid electrolyte is Li 1+a Al a Ti 2-a (PO4)3(LATP, 0≤a≤0.5).

[0074] The polymer solid electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0075] The first solvent is N-methylpyrrolidone (NMP).

[0076] The lithium salt is LiTFSI.

[0077] S2, preparation of the second sulfide solid electrolyte layer:

[0078] A second layer of slurry was coated on the basis of the first layer and dried to obtain a sulfide solid electrolyte layer. The thickness of the second layer was 15 μm.

[0079] The second layer of slurry includes a sulfide solid electrolyte, a first polymer, a lithium dendrite eliminator and a second solvent, wherein the mass ratio of the sulfide solid electrolyte, the first polymer and the lithium dendrite eliminator is 45:1:1.

[0080] The sulfide solid electrolyte is Li6PS5Cl.

[0081] The first polymer is styrene-butadiene-styrene elastomer (SEBS).

[0082] The lithium dendrite eliminator is a mixture of VO2 and TiO2.

[0083] The second solvent is toluene.

[0084] A third layer of slurry was coated on the basis of the second layer and dried to obtain a polysiloxane-based solid electrolyte layer. The thickness of the third layer was 10 μm.

[0085] The third layer slurry includes polysiloxane, the second polymer and lithium salt, wherein the mass ratio of the third layer slurry to the polysiloxane, the second polymer and the lithium salt is 20:50:50.

[0086] The lithium salt is LiTFSI.

[0087] The second polymer is polyvinylidene fluoride (PVDF).

[0088] S4, Pressing:

[0089] The first, second and third layers are rapidly hot-pressed by rollers at a certain temperature to obtain a composite solid electrolyte membrane.

[0090] Example 2

[0091] A method for preparing a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising three layers, the first layer being an oxide-polymer composite solid electrolyte layer, the second layer being a sulfide solid electrolyte layer, and the third layer being a polysiloxane-based solid electrolyte layer; the preparation method comprising the following steps:

[0092] S1, preparation of the first composite solid electrolyte layer:

[0093] The polymer porous membrane is used as a substrate and immersed in the first layer of slurry, and the first layer of slurry is used to fully fill the pores of the polymer porous membrane with ultrasound, and then dried to obtain a composite solid electrolyte layer. The thickness of the first layer is 4 μm.

[0094] The polymer porous membrane is a high-porosity PVDF-HFP membrane with a porosity of 60-80% and an equivalent pore size of 0.5-10 um.

[0095] The first layer of slurry includes an oxide solid electrolyte, a polymer solid electrolyte, a lithium salt and a first solvent, wherein the mass ratio of the oxide solid electrolyte, the polymer solid electrolyte and the lithium salt is 50:50:100.

[0096] The oxide solid electrolyte is Li 6.75 LqCy1.75 Nb 0.25 O 12 (LLZONb).

[0097] The polymer solid electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0098] The first solvent is dimethyl sulfoxide (DMSO).

[0099] The lithium salt is Li(CF3SO2)3C.

[0100] S2, preparation of the second sulfide solid electrolyte layer:

[0101] A second layer of slurry was coated on the basis of the first layer and dried to obtain a sulfide solid electrolyte layer. The thickness of the second layer was 15 μm.

[0102] The second layer of slurry includes a sulfide solid electrolyte, a first polymer, a lithium dendrite eliminator and a second solvent, wherein the mass ratio of the sulfide solid electrolyte, the first polymer and the lithium dendrite eliminator is 99:3:5.

[0103] Sulfide solid electrolyte for Li 10 GeP2S 12 .

[0104] The first polymer is an aliphatic polycarbonate (PPC).

[0105] The lithium dendrite eliminator is TiS2.

[0106] The second solvent is p-xylene.

[0107] S3, preparation of the third polysiloxane-based solid electrolyte layer:

[0108] A third layer of slurry was coated on the basis of the second layer and dried to obtain a polysiloxane-based solid electrolyte layer. The thickness of the third layer was 4 μm.

[0109] The third layer slurry includes polysiloxane, the second polymer and lithium salt, wherein the mass ratio of the third layer slurry to the polysiloxane, the second polymer and the lithium salt is 80:50:50.

[0110] The lithium salt is Li(CF3SO2)3C.

[0111] The second polymer is polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).

[0112] S4, Pressing:

[0113] The first, second and third layers are rapidly hot-pressed by rollers at a certain temperature to obtain a composite solid electrolyte membrane.

[0114] Comparative Example 1

[0115] A composite solid electrolyte membrane, the preparation method comprising the following steps:

[0116] S1, preparation of the first composite solid electrolyte layer:

[0117] The polymer porous membrane is used as a substrate and immersed in the first layer of slurry, and the first layer of slurry is used to fully fill the pores of the polymer porous membrane with ultrasound, and then dried to obtain a composite solid electrolyte layer. The thickness of the first layer is 4 μm.

[0118] S2, preparation of the second sulfide solid electrolyte layer:

[0119] The slurry was coated on glass and peeled off after drying to obtain a sulfide solid electrolyte layer. The thickness of the second layer was 15 μm.

[0120] S3, preparation of the third polysiloxane-based solid electrolyte layer:

[0121] The slurry was coated on glass and peeled off after drying to obtain a polysiloxane-based solid electrolyte layer. The thickness of the third layer was 4 μm.

[0122] S4, Pressing:

[0123] The first, second and third layers of the membrane are stacked in sequence and pressed together at a certain temperature and pressure by a hot press to obtain a composite solid electrolyte membrane.

[0124] The tensile strength, ionic conductivity and thermal shrinkage of the solid electrolyte membranes prepared in Examples 1-2 and Comparative Example 1 were tested, wherein the tensile strength and ionic conductivity tests were performed according to T / SPSTS 020-2021, and the thermal shrinkage test was performed according to GB / T 12027-2004. The test results are shown in Table 1.

[0125] Table 1 Experimental test results

[0126]

[0127] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane comprises three layers, the first layer is a composite solid electrolyte layer containing oxide-polymer, the second layer is a sulfide solid electrolyte layer, and the third layer is a polysiloxane-based solid electrolyte layer; the preparation method comprises the following steps: S1, preparation of the first composite solid electrolyte layer: Immersing a polymer porous membrane as a substrate into the first layer of slurry, using ultrasound to allow the first layer of slurry to fully fill the pores of the polymer porous membrane, and drying to obtain the composite solid electrolyte layer; S2, preparation of the second sulfide solid electrolyte layer: Coating a second layer of slurry on the basis of the first layer, and drying, to obtain the sulfide solid electrolyte layer; S3, preparation of the third polysiloxane-based solid electrolyte layer: Coating a third layer of slurry on the basis of the second layer, and drying, to obtain the polysiloxane-based solid electrolyte layer; S4, Press Fit: The first, second and third layers are rapidly hot-pressed by rollers at a certain temperature to obtain the composite solid electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: In S1, the first layer slurry includes an oxide solid electrolyte, a polymer solid electrolyte, a lithium salt and a first solvent, wherein the mass ratio of the oxide solid electrolyte, the polymer solid electrolyte and the lithium salt is (30-50): (30-50): (50-100).

3. The preparation method according to claim 1, characterized in that: In S2, the second layer slurry includes a sulfide solid electrolyte, a first polymer, a lithium dendrite eliminator and a second solvent, wherein the mass ratio of the sulfide solid electrolyte, the first polymer and the lithium dendrite eliminator is (45-99): (1-3): (1-5).

4. The preparation method according to claim 1, characterized in that: In S3, the third layer slurry includes polysiloxane, the second polymer and lithium salt, wherein the mass ratio of the third layer slurry to the polysiloxane, the second polymer and the lithium salt is (20-80):50:

50.

5. The preparation method according to claim 2, characterized in that: The oxide solid electrolyte is Li 1+a Al a Ti 2-a (PO4)3(LATP, 0≤a≤0.5), Li 1+b Al b Ge 2-b (PO4)3(LAGP, 0≤b≤0.65), La 2 / 3-c Li 3c TiO3(LLTO,0.04 <c<0.17)、La 0.56 Li 0.33+d Ti 1-d Al d O3(LLTAO, 0≤d≤0.06), Li7La3Zr2O 12 (LLZO), Li 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO) and Li 6.75 LqCy 1.75 Nb 0.25 O 12 At least one of (LLZONb); The polymer solid electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI); The first solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), acetonitrile (ACN) and dimethyl sulfoxide (DMSO).

6. The preparation method according to claim 2 or 4, characterized in that: The lithium salt is at least one of LiTFSI, LiFSI, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, LiBF4, LiBF3(C2F5), LiSCN, LiN(CN)2, LiDFOB, LiODFB, LiN(SO2F)2, LiCF3SO3, LiClO4, LiAsF6 and LiSbF6.

7. The preparation method according to claim 3, characterized in that: The sulfide solid electrolyte is Li6PS5Cl, Li2S-P2S5, Li4GeS4, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li3PS4、Li7P3S 11 At least one of; The first polymer is at least one of styrene-butadiene-styrene elastomer (SEBS), styrene-butadiene-styrene block copolymer (SBS), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), butadiene rubber (BR), natural rubber (NR) and aliphatic polycarbonate (PPC); The lithium dendrite eliminator is one or a mixture of two of VO2, TiO2, SiO2, Al2O3, MoS2, VS2, and TiS2; The second solvent is at least one of toluene, p-xylene, dichloromethane, dichloroethane, dichloropropane, dibromomethane, dibromoethane, dibromopropane, cyclohexane, n-heptane, n-decane, n-octane and anisole.

8. The preparation method according to claim 4, characterized in that: The second polymer is at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN).

9. The preparation method according to claim 1, characterized in that: In S1, the polymer porous membrane is one of a high-porosity PVDF membrane, an ePTFE membrane, a PVDF-HFP membrane, a PAN membrane, and a PMMA membrane, with a porosity of 60-80% and an equivalent pore size of 0.5-10 um.

10. The preparation method according to claim 1, characterized in that: The thickness of the first layer is 4-10 μm, the thickness of the second layer is 15-30 μm, and the thickness of the third layer is 4-10 μm.

Citation Information

Cited By

  • Sulfide electrolyte filled interpenetrating porous network ultrathin interface layer and preparation method and application thereof

    CN119994157A

  • Solid electrolyte membrane and preparation method and application thereof

    CN120497436A

  • Solid-state electrolyte membrane, method for preparing the same, and use thereof

    CN120497436B